If it's not what You are looking for type in the equation solver your own equation and let us solve it.
k in (-oo:+oo)
2*k-((4/3)*(-(5*k)-2)) = 20/3-((7*k)/3) // - 20/3-((7*k)/3)
2*k-((4/3)*(-(5*k)-2))+(7*k)/3-(20/3) = 0
(-4/3)*(-5*k-2)+2*k+(7*k)/3-20/3 = 0
2*k-4/3*(-5*k-2)+(7*k)/3-20/3 = 0
(-4/3*3*(-5*k-2))/3+(2*3*k)/3+(7*k)/3-20/3 = 0
2*3*k-4/3*3*(-5*k-2)+7*k-20 = 0
26*k+7*k-20+8 = 0
33*k-20+8 = 0
33*k-12 = 0
(33*k-12)/3 = 0
(33*k-12)/3 = 0 // * 3
33*k-12 = 0
33*k-12 = 0 // + 12
33*k = 12 // : 33
k = 12/33
k = 4/11
k = 4/11
| .04x^2+1.1x=100 | | -32-8b=-8-8(4b+3) | | 2=0.2a | | P-9=-21 | | 13x-3x+6-x=87 | | y+9=-1(x-11) | | 4x+3x-5=3 | | e^3-3e^2+4=0 | | h/6-1 | | 7/6-9/6 | | 3x+2x+4+5x-8=180 | | X^2-8x-2y+34=0 | | -9x-3=9x-4 | | y-2=-1.25(x-7) | | 6(x+5)-35x=5x+12 | | 2h/6-6=23 | | 6(x+5)-3x=5x+125 | | 24=9*3a | | -3x+4+6x=-23 | | -2x+3+4=-5x+2(3x+5) | | -11+v=-22 | | 24=c*3a | | 6(x+5)-35x=5x+125 | | 2x-5+2x-5+1x=20 | | -3x-23=-12 | | 5a+4-6a=7-a-3 | | yx-yz=x-z | | 9x+5+2+6=4x+4+9x | | y-0=-0.33333333333(x-6) | | =.07629(x)-120 | | 120e^2x=75e^3x | | -300=20x |